2005
DOI: 10.1348/147608305x27665
|View full text |Cite
|
Sign up to set email alerts
|

Who benefits from inpatient short‐term psychotherapy in the long run? Patients' evaluations, outpatient after‐care and determinants of outcome

Abstract: Attention should be given to maladaptive interpersonal relationship patterns, to vocational reintegration, and a confiding relationship as potential predictors of long-term outcome. Also, patterns of ambulatory after-care following inpatient treatment need further scrutiny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
4
14
0
1
Order By: Relevance
“…Whereas some research groups found increased therapeutic benefit for patients with higher scores on the IIP dimension affiliation [21][22][23] , others observed more positive outcomes in patients with increased scores on the IIP dimension dominance [24,25] . More consistent findings were reported with regard to the IIP mean scores, indicating a correlation between a higher amount of overall interpersonal problems and less therapeutic benefit [1,17,26] . In explorative analyses we followed the idea that within different SCL symptom profile clusters patients may benefit differentially depending on their IIP characteristics.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Whereas some research groups found increased therapeutic benefit for patients with higher scores on the IIP dimension affiliation [21][22][23] , others observed more positive outcomes in patients with increased scores on the IIP dimension dominance [24,25] . More consistent findings were reported with regard to the IIP mean scores, indicating a correlation between a higher amount of overall interpersonal problems and less therapeutic benefit [1,17,26] . In explorative analyses we followed the idea that within different SCL symptom profile clusters patients may benefit differentially depending on their IIP characteristics.…”
Section: Introductionsupporting
confidence: 71%
“…Revealing results could enable hospitals to differentially assign patients to specific treatments or potentially help improve psychotherapeutic approaches. As with other treatments and treatment settings, consistent findings, with respect to psychodynamic group psychotherapy, show that different diagnostic groups attained similar treatment outcomes [1,2] . A more complex symptom-related differentiation of inpatients using multivariate symptom profile groups may allow for better predictions of treatment outcome and, in turn, improve differential intervention strategies and the understanding of the therapeutic processes.…”
Section: Introductionsupporting
confidence: 71%
“…In the present study, patients who had already taken part in a 12-month follow-up (see Refs. [11,20]) were surveyed again 3 years after inpatient discharge.…”
Section: Long-term Outcome Of Psychodynamic Inpatient Treatmentmentioning
confidence: 99%
“…Inpatient psychotherapy is recommended if the patient's condition is very severe, if there is substantial somatic or psychic comorbidity, in prolonged sick leave, if the patients have no motivation for outpatient psychotherapy because of somatic illness concepts or if outpatient psychotherapy does not succeed in alleviating the patient's complaints. Several studies have demonstrated that the patients may derive substantial benefit in terms of improvement in global psychological and physical stress and complaints, subjective health assessment and interpersonal problems [1,2,3,4,5,6,7,8,9,10,11]. Follow-up studies have shown that these improvements are maintained over a period of time (1-year follow-up [1,2,3,4,6,9]; 3- and 3- to 5-year follow-up [7,11]).…”
Section: Introductionmentioning
confidence: 99%